IMPLEMENTASI PENDIDIKAN KARAKTER DALAM PEMBELAJARAN PPKN DI SEKOLAH DASAR - Laurentius Ni; Gonsiliana Melan; Yohanes Wendelinus Dasor (Jurnal Literasi Pendidikan Dasar (JLPD), 2021)
This study aims to explain the implementation of character education in Civics learning in elementary schools. The data collection method used is a literature study which certainly supports the research variables. The results of the study show that character education in Pancasila and civic education learning (PPKn) in elementary schools is highly applied to design character values through quality learning from planning, implementation to evaluation. The results of this study indicate that the learning process for character education is a series of learning activities both taking place in the classroom and outside the classroom that try to make students not only master the competencies (materials), but also recognize, realize/care, and internalize character values. to shape behavior. The implementation of character education in Civics learning in elementary schools goes through three stages, namely planning, implementation, and evaluation. Character education in Civics learning in elementary schools is one of the subjects that is rich in character values, therefore teachers must be able to improve their ability to manage learning effectively because Civics subjects have the potential to shape students' character which has recently been echoed.